The TH1 phenotype of follicular helper T cells indicates an IFN-γ–associated immune dysregulation in patients with CD21low common variable immunodeficiency - Unger, Susanne; Seidl, Maximilian; van Schouwenburg, Pauline; Rakhmanov, Mirzokhid; Bulashevska, Alla; Frede, Natalie; Grimbacher, Bodo; Pfeiffer, Jens; Schrenk, Klaudia; Munoz, Luis; Hanitsch, Leif; Stumpf, Ina; et al. (Journal of allergy and clinical immunology, 2018)
A subgroup of patients with common variable immunodeficiency (CVID) experience immune dysregulation manifesting as autoimmunity, lymphoproliferation, and organ inflammation and thereby increasing morbidity and mortality. Therefore treatment of these complications demands a deeper comprehension of their cause and pathophysiology. On the basis of the identification of an interferon signature in patients with CVID with secondary complications and a skewed follicular helper T-cell differentiation in defined monogenic immunodeficiencies, we sought to determine the profile of CD4 memory T cells in blood and secondary lymphatic tissues of these patients. We quantified TH1/TH2/TH17 CD4 memory T cells in blood and lymph nodes of patients with CVID using flow cytometry, analyzed their function, and correlated all findings to the burden of immune dysregulation. Patients with CVID with immune dysregulation had a skewed memory CD4 T-cell differentiation toward a CXCR3+CCR6− TH1 phenotype both in blood and lymph nodes. Consistent with our phenotypic findings, we observed a higher IFN-γ production in peripheral CD4 memory T cells and lymph node–derived follicular helper T cells of patients with CVID compared with those of healthy control subjects. Increased IFN-γ production was accompanied by a poor germinal center output, an accumulation of T-box transcription factor (T-bet)+ B cells in lymph nodes, and an accumulation of T-bet+CD21low B cells in peripheral blood of affected patients. Identification of excessive IFN-γ production by blood and lymph node–derived T cells of patients with CVID with immune dysregulation will offer new therapeutic avenues for this subgroup. CD21low B cells might serve as a marker of this IFN-γ–associated dysregulation.